Vegetation feedbacks of nutrient addition lead to a weaker carbon sink in an ombrotrophic bog. (11th October 2013) - Larmola, Tuula; Bubier, Jill L.; Kobyljanec, Christine; Basiliko, Nathan; Juutinen, Sari; Humphreys, Elyn; Preston, Michael; Moore, Tim R.
Abstract: To study vegetation feedbacks of nutrient addition on carbon sequestration capacity, we investigated vegetation and ecosystem CO2 exchange at Mer Bleue Bog, Canada in plots that had been fertilized with nitrogen (N) or with N plus phosphorus (P) and potassium (K) for 7–12 years. Gross photosynthesis, ecosystem respiration, and net CO2 exchange were measured weekly during May–September 2011 using climate‐controlled chambers. A substrate‐induced respiration technique was used to determine the functional ability of the microbial community. The highest N and NPK additions were associated with 40% less net CO2 uptake than the control. In the NPK additions, a diminished C sink potential was due to a 20–30% increase in ecosystem respiration, while gross photosynthesis rates did not change as greater vascular plant biomass compensated for the decrease in Sphagnum mosses. In the highest N‐only treatment, small reductions in gross photosynthesis and no change in ecosystem respiration led to the reduced C sink. Substrate‐induced microbial respiration was significantly higher in all levels of NPK additions compared with control. The temperature sensitivity of respiration in the plots was lower with increasing cumulative N load, suggesting more labile sources of respired CO2 . The weaker C sink potential could be explained by changes in nutrient availability, higher woody : foliar ratio, moss loss, and enhanced decomposition. Stronger responses to NPK fertilization than to N‐only fertilization for both shrub biomass production and decomposition suggest that the bog ecosystem is N‐P/K colimited rather than N‐limited. Negative effects of further N‐only deposition were indicated by delayed spring CO2 uptake. In contrast to forests, increased wood formation and surface litter accumulation in bogs seem to reduce the C sink potential owing to the loss of peat‐forming Sphagnum .